2015
DOI: 10.1016/j.neuron.2015.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Feedback Decorrelates Olfactory Bulb Output in Awake Mice

Abstract: The olfactory bulb receives rich glutamatergic projections from the piriform cortex. However, the dynamics and importance of these feedback signals remain unknown. Here, we use multiphoton calcium imaging to monitor cortical feedback in the olfactory bulb of awake mice and further probe its impact on the bulb output. Responses of feedback boutons were sparse, odor specific, and often outlasted stimuli by several seconds. Odor presentation either enhanced or suppressed the activity of boutons. However, any give… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
226
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 163 publications
(249 citation statements)
references
References 76 publications
(95 reference statements)
22
226
1
Order By: Relevance
“…S4). Two recent reports have described spontaneous calcium transients in boutons on corticobulbar axons in the OB (33,34). Their presence implies that the sources of those axons, SP cells in the anterior PC (42), are also spontaneously active, consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…S4). Two recent reports have described spontaneous calcium transients in boutons on corticobulbar axons in the OB (33,34). Their presence implies that the sources of those axons, SP cells in the anterior PC (42), are also spontaneously active, consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…However, it remains possible that intracortical and descending inputs could contribute to spontaneous activity in the awake state. The anterior PC also sends corticobulbar axons back to the OB (32,33,41), but, again, we found no evidence for the contribution of a reciprocal OB ↔ PC loop in the generation of spontaneous excitation in the PC (Fig. S4).…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Anesthesia affects olfactory circuits in nuanced ways that may not be equivalent to simple scaling of responses in individual cells (Kato et al, 2012; Otazu et al, 2015). Therefore, we directly compared the responses of young and mature abGC dendrites in the awake versus the anesthetized state to odor set C (Figures 6A, 6B).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesize that the proximity of centrifugally projecting neurons to each another allows them to interact through local inhibitory connections (Poo and Isaacson, 2009; Suzuki and Bekkers, 2010). By synthesizing the activity of local ensembles of neurons (Zelano et al, 2011), clustered feedback may further sparsen incoming odor representations in the MOB (Otazu et al, 2015). In addition, recent theoretical work has shown that clustered connectivity can give rise to complex temporal patterns of activity on long time scales (Litwin-Kumar and Doiron, 2012).…”
Section: Discussionmentioning
confidence: 99%